The Stressing Factors in Clinical Education: The Viewpoints of Students - Mohammadreza Yazdankhah Fard; Shahnaz Pouladi; Farahnaz Kamali; Nasrin Zahmatkeshan; Kamran Mirzaei; Sherafat Akaberian; Siamak Yazdanpanah; Tayebeh Jamand; Tayebeh Gharibi; Rozita Khorramroudi (مجله ایرانی آموزش در علوم پزشکی, 2009)
Introduction: Clinical education is a complicated process which is affected by several factors and variables. Thus the aim of this study was to determine the stressing factors in clinical education from the viewpoints of students of Boushehr University of Medical Sciences. Methods: In this descriptive cross-sectional study, 334 students of Boushehr University of Medical Sciences were selected thorough census. The data gathering tool was a researcher-made questionnaire. This question-naire consisted of two parts of demographic data and 60 questions about stressing factors in clinical educa-tion in five areas. Data was analyzed by SPSS software using frequency distribution, mean, standard devia-tion, and Chi², variance analysis test. Results: The humiliating experiences, educational environment, clinical experiences, unpleasant emotions, and interpersonal relationships areas were high stressing factors respectively. The most stressing factors were as teachers' notification in front of personnel and physicians, lack of facilities in ward, watching patients suffering from pain, solicitude about contagious disease transmission, and lack of teacher support respectively. Conclusion: Medical students are exposed to a variety of stressor factors. Thus establishing a supportive system during the first academic year and improving it throughout clinical education is necessary to equip medical students with effective coping skills.